2020
DOI: 10.1128/msphere.00255-20
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Segregation in Bacillus subtilis Follows an Overall Pattern of Linear Movement and Is Highly Robust against Cell Cycle Perturbations

Abstract: Although several proteins have been identified that facilitate chromosome segregation in bacteria, no clear analogue of the mitotic machinery in eukaryotic cells has been identified. In order to investigate if recognizable patterns of segregation exist during the cell cycle, we tracked the segregation of duplicated origin regions in Bacillus subtilis for 60 min in the fastest practically achievable resolution, achieving 10-s intervals. We found that while separation occurred in random patterns, often including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 68 publications
4
38
2
Order By: Relevance
“…These ndings show that although MMC induces events of replication arrests due to interstrand crosslinks, and leads to atypical nucleoid morphology, most MMC-treated cells were still able to complete a replication cycle, or even reinitiated another cycle, giving rise to a double set of chromosomes after induction of DNA damage. The ndings are in accordance with the report that MMC slows down the cell cycle considerably but does not stop it completely [6], and with ndings from Goranov et al showing that double strand breaks induced by MMC slow down the replication elongation beyond the origin proximal region [10].…”
Section: Estimation Of the Number Of Nuclei Based On Dapi Uorescencesupporting
confidence: 92%
“…These ndings show that although MMC induces events of replication arrests due to interstrand crosslinks, and leads to atypical nucleoid morphology, most MMC-treated cells were still able to complete a replication cycle, or even reinitiated another cycle, giving rise to a double set of chromosomes after induction of DNA damage. The ndings are in accordance with the report that MMC slows down the cell cycle considerably but does not stop it completely [6], and with ndings from Goranov et al showing that double strand breaks induced by MMC slow down the replication elongation beyond the origin proximal region [10].…”
Section: Estimation Of the Number Of Nuclei Based On Dapi Uorescencesupporting
confidence: 92%
“…These ndings show that despite frequent replication arrests due to interstrand crosslinking by MMC and the atypical nucleoid morphology, many cells were either still able to complete a replication cycle and had a double set of chromosomes after induction of DNA damage, or that the cells simply retained the number of nucleoids and termini they had before damage induction. The latter is in accordance with the idea that MMC slows down the cell cycle considerably but does not stop it completely [6]. Goranov et al showed that double strand breaks induced by MMC inhibit the replication elongation beyond the origin proximal region [10].…”
Section: Estimation Of the Number Of Nuclei Based On Dapi Uorescencesupporting
confidence: 86%
“…As stated in reference [6], a small fraction of cells containing the FROS system showed irregularities in segregation. Cells were taken from exponential growth conditions and were imaged within 10 minutes, minimally in uencing the actual number of origins and termini.…”
Section: Limitationsmentioning
confidence: 60%
“…We propose that this exchange is based on exchange of subunits from the hexameric helicase, which thus appear to exchange within a time frame of few seconds. We have recently shown that chromosome segregation and thus also DNA replication, which occur concomitantly, are relatively robust against DNA damageinduction via MMC or inhibition of DNA gyrase, continuing to follow a general pattern that resembles that of directed diffusion (48). Here, we show that replication forks can be seen…”
Section: Stress Conditions Differentially Affect Dwell Times Of Dnacmentioning
confidence: 53%
“…S3). Because chromosome segregation and thus replication continue after addition of MMC, albeit more slowly (48), likely based on frequent restart processes, it follows that DnaC molecules are more frequently exchanged during replication restart than polymerases. Unexpectedly, blocking of PolC by HPUra lead to an increase of fork-bound primase molecules (Fig.…”
Section: Dnac Dnag and Dnae Respond Differentially To Stress Conditimentioning
confidence: 99%